Transcriptional control and exploitation of an immune‐responsive family of plant retrotransposons - Zervudacki, Jérôme (EMBO J, 2018)
Mobilization of transposable elements (TEs) in plants has been recognized as a driving force of evolution and adaptation, in particular by providing genes with regulatory modules that impact their transcription. In this study, we employed an ATCOPIA93 long‐terminal repeat (LTR) promoter‐GUS fusion to show that this retrotransposon behaves like an immune‐responsive gene during pathogen defense in Arabidopsis. We also showed that the endogenous ATCOPIA93 copy “EVD”, which is activated in the presence of bacterial stress, is negatively regulated by both DNA methylation and polycomb‐mediated silencing, a mode of repression typically found at protein‐coding and microRNA genes. Interestingly, an ATCOPIA93‐derived soloLTR is located upstream of the disease resistance gene RPP4 and is devoid of DNA methylation and H3K27m3 marks. Through loss‐of‐function experiments, we demonstrate that this soloLTR is required for the proper expression of RPP4 during plant defense, thus linking the responsiveness of ATCOPIA93 to biotic stress and the co‐option of its LTR for plant immunity.